The Minamata Treaty / Protocol: Potential Implications for South Africa - Scott, G.M.; Mdluli, T.N. (Clean Air Journal, 2012)
In 2009 the United Nations Environment Programme (UNEP) was mandated by its Governing Council to develop a global legally binding instrument for mercury. An Intergovernmental Negotiating Committee (INC) was established to prepare the instrument before the 27th UNEP Governing Council Meeting in February 2013. This instrument will have significant and far-reaching effects for South Africa, due to our economy’s reliance on fossil fuels, in particular coal fired power generation. South Africa is currently rated as the 6th largest emitter of mercury in the world with annual emissions estimated at around 50 tons. This paper will look at the draft text of the instrument after the 4th round of negotiations and highlight some of the potential implications for South Africa. It must be highlighted that the text of the instrument is still under negotiations and the observations and remarks made in this paper are not the official position of the Government of South Africa.